2021
DOI: 10.1016/j.tranon.2020.100999
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of perioperative levels of DNA and mRNA in plasma of patients with renal cell carcinoma

Abstract: Highlights Plasma levels of GAPDH cfDNA might be useful as complementary methods for diagnosis and prognosis of renal cell carcinoma. Pre and postoperative levels of GAPDH cfDNA were independently associated with OS in renal cell carcinoma. hTERT cfRNA was not a marker useful for diagnosis nor prognosis of renal cell cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As shown in Figure 1 , careful screening and verification identified eight studies that were eligible for meta-analysis. The main characteristics and details of these eligible studies Salinas-Sanchez et al (2021) , Lasseter et al (2020) , Yamamoto et al (2018) , Lu et al (2016) , Wan et al (2013) , De Martino et al (2012) , Ellinger et al (2012) , Hauser et al (2010) are summarized in Table 1 . These eight eligible studies featured a total of 754 patients, with a median sample size of 87 (range: 33–229, mean: 94).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 1 , careful screening and verification identified eight studies that were eligible for meta-analysis. The main characteristics and details of these eligible studies Salinas-Sanchez et al (2021) , Lasseter et al (2020) , Yamamoto et al (2018) , Lu et al (2016) , Wan et al (2013) , De Martino et al (2012) , Ellinger et al (2012) , Hauser et al (2010) are summarized in Table 1 . These eight eligible studies featured a total of 754 patients, with a median sample size of 87 (range: 33–229, mean: 94).…”
Section: Resultsmentioning
confidence: 99%
“…Cf-DNA was primarily detected by next generation sequencing or PCR-based method, and it could be characterized by composition (size, fragment or integrity), concentration (total, panel or specified gene) or genetic characteristics (methylation or nucleotide variants) ( Table 1 ). Of these, three studies extracted DNA from serum Hauser et al (2010) , De Martino et al (2012) , Ellinger et al (2012) , while the other five studies extracted DNA from plasma ( Wan et al, 2013 ; Lu et al, 2016 ; Yamamoto et al, 2018 ; Lasseter et al, 2020 ; Salinas-Sanchez et al, 2021 ). The blood volume required for the detection of cf-DNA varied from 0.8 to 3 ml.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cell-free nucleic acids have obvious potential for monitoring postoperative outcomes. Plasma GAPDH and hTERT cfDNA levels decreased significantly postoperatively and correlated with the risk of postoperative progression and death [ 191 ]. One study reported that each fg/mL of postoperative GAPDH cfDNA and hTERT cfDNA increased the risk of progression by 1.04 and 1.2 in Patients with RCC, respectively.…”
Section: Introductionmentioning
confidence: 99%